Precise Control of Lamellar Thickness in Highly Oriented Regioregular Poly(3‐Hexylthiophene) Thin Films Prepared by High‐Temperature Rubbing: Correlations with Optical Properties and Charge Transport. (7th December 2015) - Hamidi‐Sakr, Amer; Biniek, Laure; Fall, Sadiara; Brinkmann, Martin
Abstract : Precise control of orientation and crystallinity is achieved in regioregular poly(3‐hexylthiophene) (P3HT) thin films by using high‐temperature rubbing, a fast and effective alignment method. Rubbing P3HT films at temperatures T R ≥ 144 °C generates highly oriented crystalline films with a periodic lamellar morphology with a dichroic ratio reaching 25. The crystallinity and the average crystal size along the chain axis direction, l c, are determined by high‐resolution transmission electron microscopy and differential scanning calorimetry. The inverse of the lamellar period l scales with the supercooling and can accordingly be controlled by the rubbing temperature T R . Uniquely, the observed exciton coupling in P3HT crystals is correlated to the length of the average planarized chain segments l c in the crystals. The high alignment and crystallinity observed for T R > 200 °C cannot translate to high hole mobilities parallel to the rubbing because of the adverse effect of amorphous zones interrupting charge transport between crystalline lamellae. Although tie chains bridge successive P3HT crystals through amorphous zones, their twisted conformation restrains interlamellar charge transport. The evolution of charge transport anisotropy is correlated to the evolution of the dominant contact plane from mainly face‐on ( T R ≤ 100 °C) to edge‐on ( T R ≥ 170 °C). Abstract : Precise control of orientation and crystallinity is achieved in regioregular poly(3‐hexylthiophene) (P3HT) thin films by using high‐temperature rubbing, a fast and effective alignment method. Uniquely, the exciton coupling in P3HT is correlated to the length of the planarized chain segments in the crystals. The evolution of charge transport versus rubbing temperature is correlated to the crystal orientation and film nanomorphology.